Water Quality of Surface Waters in Lower Euphrates Basin (Southeastern Anatolia, Turkey) - Alp, Mehmet Tahir; Kocer, Mehmet A. T.; Sen, Bulent; Ozbay, Ozgur (Medwell Online, 2010)
In this study, some physicochemical properties of surface waters of the lower Euphrates Basin in the Southeastern Anatolia region were investigated The water sources investigated are Ataturk, Birecik, Karkamis and Ham Hidir Dam lakes and Euphrates River together with eight streams which are major running waters of the sub-basin Total 20 variables consisting of temperature, pH, electrical conductivity, dissolved oxygen, turbidity, total dissolved and suspended solids, biochemical oxygen demand, total hardness, total alkalinity, calcium, magnesium, sodium, potassium, chloride, fluoride, sulfate, ammonia nitrogen, nitrate nitrogen and reactive phosphorus were monitored in surface waters Significant relationships between dissolved ions, conductivity, hardness and alkalinity were observed While most of the surface waters had middle hard and slightly alkaline characteristics with moderate dissolved solids and low organic matter content, Haci Hidir Dam lake and Nizip Stream separated from them in terms of investigated variables
Keywords: Lower Euphrates; surface waters; water quality; Southeastern Anatolia; conductivity; investigated variable